The Effect of Micro-oxygenation on the Phenolic Composition, Quality and Aerobic Wine-Spoilage Microorganisms of Different South African Red Wines - du Toit, W.J.; Lisjak, K.; Marais, J.; du Toit, M. (South African Journal of Enology and Viticulture, 2017)
The effect of micro-oxygenation treatments on the composition of different South African red wines was evaluated. In some wines, micro-oxygenation led to an increase in colour density, with a corresponding change in colour, due to the formation of polymeric pigments. This increase also led to the red colour becoming more resistant to the bleaching effect of SO2. Micro-oxygenation also seemed to be more effective in increasing the colour densities of younger red wines than the older ones, although total red pigments were found to be highest in an older red wine that had received micro-oxygenation. Differences in the gelatine index were also observed over time. The micro-oxygenated and barrel-matured wines also had lower concentrations of catechin and the procyanidin B1, and showed a corresponding increase in polymeric pigment and polymeric phenols. Micro-oxygenation led to higher acetic acid bacteria counts, although no increase in volatile acidity was observed in these wines. A tasting panel preferred younger red wines that had undergone micro-oxygenation. In an older red wine prolonged micro-oxygenation led to the wine becoming over-aged, with an increase in the barnyard/medicinal character, which corresponded with an increase in Brettanomyces counts. Micro-oxygenation can be used to increase the quality of young red wines, but further research is needed in this area.